جمالية العجيب في المجموعة القصصية المتحولين لوفاء عبد الرزاق - حمزة, حمادة; بوردحة, أسماء; مستور, إيمان; عمامرة, سمية (University of Eloued جامعة الوادي, 2024)
تمثل العجائبية شكلا من أشكال التعبير الجديدة، حيث تقوم هذه التقنية السردية على كسر ما هو مألوف وما هو واقعي طبيعي، فتخترق الحدود والمنطق، وتثير الاستغراب والتردد، مما يستدعي من القارئ الدهشة والحيرة والتعجب، لذا نجد النصوص الحكائية العجائبية تخلق ترقباً دائما لوقوع أحداث جديدة لم تكن متوقعة، بل تحفز القارئ على خلق تفسيرات وتخيلات وتوقعات لم تخطر حتى ببال مبدعها، فتعمل على توسيع أفق التأويل وتزيد من جمالية النص. إن النصوص الحكائية العجائبية لا تكمن عجائبيتها في الأحداث والأماكن فقط، بل أيضا في لغتها وشخصياتها، فقد استطاعت القاصة وفاء عبد الرزاق أن تتجاوز هذا الواقع لتصل إلى اللاواقع من خلال التعجيب والتغريب، وإضفاء صبغة عجائبية عليه من خلال التحولات الحاصلة نتيجة صراعات داخلية جعلتها تفعّل ملكة الخيال كسبيل للهروب من واقعها المؤلم والموحش، لقد استطاعت الكاتبة التلاعب بالزمن و التنقل بكل سهولة بين الماضي و المستقبل عن طريق التقنيات المستخدمة في البناء الروائي على سبيل الاسترجاع أو الاستباق أو الحذف وغيرهم، وهذا مما يساهم في تشكيل النص العجائبي و يخلق في الأحداث تصورا جماليا كما أن حسن توظيفها للشخصيات التي لها علاقة بالموروث الشعبي أو الدين أو الأسطورة عنصرا فاعلا دل على تحكمها في توظيف هذه المصادر للعجيب بالإضافة إلى القدرة على توظيف اللغة فكل هذه العناصر أبرزت الجمالية. الفن القصصي هو استلهام للواقع ثم ارتقاء للصورة الإبداعية عن طريق التخييل، كون الحكايات تدور حول المخلوقات العجيبة مشكلة بذلك أحداثا متنوعة بين خيالية وأخرى واقعية. The fantastical represents a form of new expression، where this narrative technique breaks what is familiar and realistically natural. It penetrates boundaries and logic، evoking astonishment and hesitation، which prompts the reader to experience wonder، confusion، and amazement. Therefore، we find that fantastical narrative texts always create anticipation for the occurrence of new and unexpected events. They stimulate the reader to generate interpretations، imaginations، and expectations that may not have even occurred to their creator، thereby expanding the horizon of interpretation and enhancing the beauty of the text. The fantastical nature of narrative texts does not lie solely in the events and places، but also in their language and characters. The writer Wafaa Abdul Razzaq has managed to transcend reality to reach the non-reality through fantastical and estranging elements، imparting a fantastical tone through the transformations resulting from internal conflicts. These conflicts have activated her imagination as a means of escaping her painful and bleak reality. The author has skillfully manipulated time، effortlessly moving between the past and the future using narrative techniques such as flashbacks، foreshadowing، and omission، among others. This contributes to shaping the fantastical text and creates an aesthetic perception of the events. Additionally، her adept use of characters related to folklore، religion، or myth has demonstrated her control over utilizing these sources of the fantastical، along with her ability to employ language effectively. All these elements have highlighted the aesthetic quality. Storytelling art is an inspiration drawn from reality، elevated to a creative image through imagination. The tales revolve around fantastical creatures، thereby creating diverse events that blend fantasy with reality.
أدب حديث ومعاصر
Keywords: القصص – العجائبية- المنهج الجمالي; Stories - Marvelous - Aesthetic Approach